Insiders, outsiders, and agents of change: First person action inquiry in community sport management. Issue 1 (February 2017) - Rich, Kyle A.; Misener, Laura
Highlights: Reflexivity can be explicitly used as a methodological tool for improving the process and products outcomes of sport management research for multiple stakeholders. Iterative cycles of Reflection and -discussion cycles can be used to navigate methodological and ethical tensions that arise while doing of insider action research. First-person inquiry Reflexivity is a useful approach for navigating complex community contexts and understanding researcher the roles and limitations of researchers in the research process. Action research approaches offer diverse perspectives and paradigms that may be beneficial for sport management researchers and practitioners. Abstract: Using first-person inquiry, we explore the use of reflexive practice as a means of self-study in community sport management research. In the context of a participatory action research project with a rural Northern Ontario community recreation committee, we describe our process of conducting first person action inquiry, explore how it enriched the process and outcomes of the project, and explain how it informed our understanding of researchers (ourselves) as instruments of research and agents of change within the research process. Through the process of self-study and iterative discussions between a graduate student (sometimes) insider and academic supervisor outsider, we demonstrate how reflexive practice led to a better understanding of community contexts as well as the roles and limitations of the researchers therein. Consequently, reflections allowed for a moulding of the methodological approach to be more effective (for research and action) with(in) the community. Based on our discussion, we highlight the potential of diverse research practices and paradigms to offer new perspectives for sport management research and practice.